2021
DOI: 10.3390/pharmaceutics13101620
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Liquid Formulations Based on Low Transition Temperature Mixtures for the Incorporation of Anti-Inflammatory Drugs

Abstract: Most nonsteroidal anti-inflammatory drugs (NSAIDs) present poor aqueous solubility, impairing their efficiency in physiological media. In this context, Low Transition Temperature Mixtures (LTTMs) are a promising platform to overcome drugs’ poor solubility, forming therapeutic liquid formulations. In this work, the LTTMs of citric acid:L-arginine:water (C:A:W) and glycerol:sorbitol (G:S) were studied in terms of their features and assessed in terms of their ability to increase the solubility of six NSAIDs in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…The increase in T g might be related to an increased crosslinking, which reduces the flexibility of the polymer chain indicating stronger material. Moreover, in the samples containing SR as a crosslinker, a second endothermic event occurred at ~95°C which could be due to unreacted SR 46,47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in T g might be related to an increased crosslinking, which reduces the flexibility of the polymer chain indicating stronger material. Moreover, in the samples containing SR as a crosslinker, a second endothermic event occurred at ~95°C which could be due to unreacted SR 46,47 …”
Section: Resultsmentioning
confidence: 99%
“…The increase in T g might be related to an increased crosslinking, which reduces the flexibility of the polymer chain indicating stronger material. Moreover, in the samples containing SR as a crosslinker, a second endothermic event occurred at $95 C which could be due to unreacted SR. 46,47 3.7 | Gel content and swelling Figure 9 represents the swelling and gel content values of the adhesives cured at room temperature in water and toluene. Water has shown less effect on the samples' properties in terms of gelling and swelling.…”
Section: Dscmentioning
confidence: 99%
“…Despite the fact that the extent of their environmental friendliness has recently become a topic of debate [74][75][76][77], DESs showcase remarkable potential across various domains of pharmaceutical applications, including drug synthesis, formulation, and extraction processes [78][79][80][81][82][83][84][85][86][87][88]. Noteworthily, DESs have been shown to be effective solubilizers of ibuprofen [89,90] and ketoprofen [91]. As it can be seen, a substantial dataset has emerged, which serves as an intriguing starting point for modeling the solubilization properties of both examined active substances.…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing the solvation interactions (i.e., dipolarity/polarizability, dispersion, hydrogen-bonding, n –π, and π–π interactions) is of utmost importance to fully exploit the designer aspects of API DESs where the API can be employed as HBA, HBD, or HBA and HBD and to understand the complex interplay between the HBA and HBD in API DESs. Several studies have reported the preparation and applications of API DESs using different APIs such as aspirin, ibuprofen, lidocaine, and prilocaine with excipients (molecules that deliver the active ingredient to active site) such as carboxylic acids, long-chain alcohols, and choline chloride. ,, However, studies that evaluate their polarity and intermolecular solvation interactions are very limited. Single polarity scales such as Reichardt’s polarity index and Nile red polarity scale have been used for DESs. Kamlet–Taft parameters have also been employed to separately quantify the dipolarity/polarizability (π*), hydrogen-bond-accepting ability (β), and hydrogen-bond-donating ability ( a ) . Saha et al.…”
Section: Introductionmentioning
confidence: 99%